THE USE OF AUDIO VISUAL MEDIA IN TEACHING SPEAKING - Feri Kurniawan (English Education Journal, 2016)
This study focused on teaching speaking skills using Audio Visual Media to year eight students at SMP T. Bustanul Arifin, in Bener Meriah District, Aceh Province. This study compared results of the students’ achievements in speaking before and after using the Audio Visual Media (AVM) method of teaching. The population of this study was 154 students and the sample was 18 students from class VIII-1. The data were analyzed, and the results showed that the average score from the pre-test was 58, while the post-test score was 67, an improvement of 9 points. There was an improvement in four aspects of speaking: Pronunciation improved from 12 to 16, grammar from 12 to 14, vocabulary from 12 to 15, whilst fluency hardly increased at all and comprehension did not improve. Based on the data, pronunciation was the most improved by the AVM method. There was an improvement of the students in speaking after the students were taught by using the AVM method. The results indicate that the students had a positive response to using the AVM as 92% of the responses were positive towards the use of the AVM method for teaching speaking. Therefore, it is suggested that English teachers who have similar problems should try using AVM for teaching speaking.